2004
DOI: 10.1093/brain/awh303
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of pathological involvement of the striatonigral and olivopontocerebellar systems in multiple system atrophy: clinicopathological correlations

Abstract: Multiple system atrophy (MSA) has varying clinical (MSA-P versus MSA-C) and pathological [striatonigral degeneration (SND) versus olivopontocerebellar atrophy (OPCA)] phenotypes. To investigate the spectrum of clinicopathological correlations, we performed a semi-quantitative pathological analysis of 100 MSA cases with well-characterized clinical phenotypes. In 24 areas, chosen from both the striatonigral (StrN) and olivopontocerebellar (OPC) regions, the severity of neuronal cell loss and gliosis as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

42
437
6
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 461 publications
(487 citation statements)
references
References 44 publications
42
437
6
2
Order By: Relevance
“…While patients with MSA can have clinical parkinsonism without ataxia, and vice versa, data from a recent clinicopathologic study from 100 patients with MSA suggest that basal ganglia and cerebellar regional pathology do not exist in isolation. 26 Furthermore, although the putamen and cerebellum are key elements of the MSARP topography, this metabolic network includes significant contributions from other brain areas.…”
Section: Discussionmentioning
confidence: 99%
“…While patients with MSA can have clinical parkinsonism without ataxia, and vice versa, data from a recent clinicopathologic study from 100 patients with MSA suggest that basal ganglia and cerebellar regional pathology do not exist in isolation. 26 Furthermore, although the putamen and cerebellum are key elements of the MSARP topography, this metabolic network includes significant contributions from other brain areas.…”
Section: Discussionmentioning
confidence: 99%
“…Ozawa et al performed a semi-quantitative analysis of pathological changes in the striatonigral and olivopontocerebellar regions of 100 MSA patients with well-characterized clinical phenotypes, and reported that MSA-P was predominantly associated with striatonigral changes, while olivopontocerebellar pathology was prominent in MSA-C [4]. They also suggested that the pathological threshold for the clinical onset of parkinsonism was lower than that for ataxia [4]. This may explain why parkinsonian features become dominant over cerebellar features in some MSA-C patients.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical decline is much more rapid than occurs in PD; a retrospective study found that about 40% of patients were markedly disabled or wheelchair bound within 5 years of onset of motor disturbance. The neuropathology is characterised by glial cytoplasmic inclusions and neuronal atrophy which selectively a¡ect the basal ganglia, pons and cerebellum [Ozawa et al, 2004] as well as parts of the central nervous system concerned with bladder control.…”
Section: Differential Diagnosis Of Pd In Patients With Urinary Incontmentioning
confidence: 99%